Carbon fiber/polyetherketoneketone composites. Part I: An ideal and uniform composition via solution‐based processing. Issue 5 (4th March 2022) - Li, Bolan; Zhang, Feng; Jiao, Mengxiao; Li, Yanbo; Wang, Xin; Zhang, Xiaohua
Abstract: As limited by the low dissolubility, powder‐ and dispersion‐based composition methods are used to prepare carbon fiber (CF)/polyaryletherketone (PAEK) prepregs. Owing to the high content of ketone groups, polyetherketoneketone (PEKK) is found to have a high dissolubility in fluorine‐ and/or chlorine‐containing solvents. It is revealed that PEKK can form colloidal solutions with a particle size down to tens of nm, paving the way for a true solution‐based impregnation toward advanced CF/PEKK composites. After a fabrication route of impregnation, preheating, and compression molding, PEKK was found to uniformly and tightly cover all the CFs within a thickness of 1–3 μm in the final composites. Such limited spacing and the fiber surface strongly suppress the crystallization of PEKK. As a result, the composites exhibited a tensile strength of 1.85 GPa, 94.9% that of the ideal one according to the rule of mixture. Abstract :